MANAJEMEN PENGEMBANGAN KURIKULUM BERBASIS ASESMEN KEBUTUHAN DI LEMBAGA PENDIDIKAN ISLAM - Istiqomah; Ahmad Salabi; Yahya Mof (Ar-Rasyid: Jurnal Publikasi Penelitian Ilmiah, 2026)
This study aims to analyze curriculum development management based on needs assessment in Islamic educational institutions and explain the importance of implementing needs assessment in creating relevant and adaptive curricula. This study employed a library research method with a descriptive qualitative approach. Data were collected through documentation studies from various scientific journals, books, and articles relevant to the research topic. The data were analyzed using content analysis through data reduction, data presentation, interpretation, and conclusion drawing. The findings indicate that needs assessment plays an important role in identifying the needs of students, institutions, and society as the basis for curriculum development. The stages of curriculum development management include planning, organizing, implementation, and evaluation, which must be carried out systematically. In addition, Islamic educational institutions face various challenges such as limited human resources, technological developments, and the need to maintain a balance between scientific knowledge and Islamic values. Therefore, curriculum development based on needs assessment is considered an effective strategy to improve the quality of Islamic education in order to remain relevant, adaptive, and grounded in Islamic values.